The integration of social media and marketing strategy : tactics, strategy, and culture - Li, Fang Fang (Vaasan yliopisto, 2022)
Social media (SM) has become a promising marketing tool to achieve firms’ business goals and competitive advantages. Despite the popularity of SM marketing, incorporating SM into firms’ marketing strategies is an ongoing challenge, especially for international firms who are using SM in global markets. In this dissertation, the author aims to advance the understanding of the integration of SM and marketing strategy and its application in the international marketing context. The key objective is to answer the following research questions: What are the impacts of SM on marketing and how can SM be strategically utilized and managed, especially in an international marketing setting? This study draws on the resource-based view, the dynamic capabilities approach, and customer engagement theory. The dissertation consists of four papers and adopts a mixed-method approach, including both qualitative and quantitative research designs. Through a comprehensive and systematic review of SM marketing research (N=327 articles), the study shows SM is radically transforming the key marketing functions, such as selling, communications, and customer relationship management. This study conceptualizes social media marketing strategy (SMMS) from SM and marketing strategy dimensions and identifies four SMMSs, namely, social commerce strategy, social content strategy, social monitoring strategy, and social CRM strategy. The study also suggests that customer engagement can be regarded as a desirable marketing performance metric, as it reflects the outcome of connectedness and interaction on SM. Cultural value greatly impacts firms’ SMMS developmental process and consumer attitudes and interactions on SM. Therefore, this study suggests firms use SM more strategically and understand its culture-bound nature. This research thus makes great theoretical contributions to different research fields and provides useful managerial implications for SM marketing management.

Sosiaalisesta mediasta on tullut lupaava markkinointiväline. Suosiosta huolimatta sosiaalisen median sisällyttäminen yritysten markkinointistrategioihin on jatkuva haaste erityisesti kansainvälisille yrityksille, jotka käyttävät sosiaalista mediaa markkinoinnissaan globaaleilla markkinoilla. Tässä väitöskirjassa lisätään ymmärrystä sosiaalisen median ja markkinointistrategian integroinnista ja sosiaalisen median soveltamisesta kansainväliseen markkinointiin. Tavoitteena on vastata tutkimuskysymyksiin: Mitkä ovat sosiaalisen median vaikutukset markkinointiin ja miten sitä voidaan hyödyntää ja hallita strategisesti erityisesti kansainvälisessä markkinointiympäristössä? Tutkimus perustuu resurssipohjaiseen näkemykseen, dynaamisten kyvykkyyksien lähestymistapaan ja asiakkaan sitoutumisen teoriaan. Väitöskirja koostuu neljästä artikkelista ja soveltaa sekä kvalitatiivisia että kvantitatiivisia tutkimusasetelmia. Tutkimus osoittaa kattavan kirjallisuuskatsauksen (327 artikkelia) avulla, että sosiaalinen media muuttaa radikaalisti keskeisiä markkinointitoimintoja, kuten myyntiä, viestintää ja asiakassuhteiden hallintaa. Tutkimuksessa käsitteellistetään sosiaalisen median markkinointistrategia (SMMS) ja yksilöidään neljä SMMS:ää: sosiaalisen median kaupankäynnin strategia, sisältöstrategia, seurantastrategia ja asiakkuudenhallinnan strategia. Tutkimuksessa ehdotetaan, että asiakkaiden sitoutumista voidaan pitää toivottavana markkinoinnin suorituskyvyn mittarina, koska se kuvastaa yhteyksien ja vuorovaikutuksen tulosta sosiaalisessa mediassa. Kulttuurinen arvo vaikuttaa suuresti yritysten SMMS-kehitysprosessiin sekä kuluttajien asenteisiin ja vuorovaikutukseen sosiaalisessa mediassa. Tutkimuksessa ehdotetaankin, että yritykset käyttäisivät sosiaalista mediaa strategisemmin ja ymmärtäisivät sen kulttuurisidonnaisuudet. Tutkimus antaa mittavan teoreettisen panoksen eri tutkimusaloille ja tarjoaa hyödyllistä tietoa yrityksille sosiaalisen median markkinoinnin johtamiseen.
Sosiaalisen median ja markkinointistrategian integrointi : taktiikat, strategia ja kulttuuri
Keywords: marketing strategies; social media marketing; customer engagement; culture; international marketing; marketing; social media; media; corporate strategies; new media; strategies; pictorial communication; brands; customs (culture); fi=Kansainvälinen liiketoiminta|en=International Business|